Dentate Gyrus Peroxiredoxin 6 Levels Discriminate Aged Unimpaired From Impaired Rats in a Spatial Memory Task - Lubec, Jana; Smidak, Roman; Malikovic, Jovana; Feyissa, Daniel Daba; Korz, Volker; Höger, Harald; Lubec, Gert (Frontiers in Aging Neuroscience, 2019)
Similar to humans, the normal aged rat population is not homogenous in terms of cognitive function. Two distinct subpopulations of aged Sprague-Dawley rats can be identified on the basis of spatial memory performance in the hole-board paradigm. It was the aim of the study to reveal protein changes relevant to aging and spatial memory performance. Aged impaired (AI) and unimpaired (AU) male rats, 22-24 months old were selected from a large cohort of 160 animals; young animals served as controls. Enriched synaptosomal fraction from dentate gyrus from behaviourally characterized old animals were used for isobaric tags labelling based quantitative proteomic analysis. As differences in peroxiredoxin 6 (PRDX6) levels were a pronounced finding, PRDX6 levels were also quantified by immunoblotting. AI showed impaired spatial memory abilities while AU performed comparable to young animals. Our study demonstrates substantial quantitative alteration of proteins involved in energy metabolism, inflammation and synaptic plasticity during aging. Moreover, we identified protein changes specifically coupled to memory performance of aged rats. PRDX6 levels clearly differentiated AI from AU and levels in AU were comparable to those of young animals. In addition, it was observed that stochasticity in protein levels increased with age and discriminate between AI and AU groups. Moreover, there was a significantly higher variability of protein levels in AI. PRDX6 is a member of the peroxiredoxin family and well-defined as a cystein-1 PRDX that reduces and detoxifies hydroxyperoxides. It is well-known and documented that the aging brain shows increased active oxygen species but so far no study proposed a potential target with antioxidant activity that would discriminate between impaired and unimpaired memory performers. Current data, representing so far the largest proteomics data set in aging DG, provide first evidence for a probable role of PRDX6 in memory performance.